2014
DOI: 10.1149/2.0461503jes
|View full text |Cite
|
Sign up to set email alerts
|

An Alkaline Flow Battery Based on the Coordination Chemistry of Iron and Cobalt

Abstract: We present the first alkaline redox flow battery (a-RFB) based on the coordination chemistry of cobalt with 1-[Bis(2-hydroxyethyl)amino]-2-propanol (mTEA) and iron with triethanolamine (TEA) in 5 M NaOH. The overall redox system has a cell voltage of 0.93 V in the charged state. Importantly, the coordination compounds are negatively charged and have limited transport through the cation exchange membrane (e.g., Nafion), minimizing the extent of redox species crossover during charge-discharge cycling. Fe-TEA is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 20 publications
(22 reference statements)
1
39
0
Order By: Relevance
“…The next-generation of RFB chemistries are likely to be engineered molecules or complexes, since this approach enables one to shift the SRP to a more desirable potential. One approach that has been utilized to do this is ligand-modified transition metals, which can be dissolved in aqueous 19 or non-aqueous 20 electrolyte solutions. Another promising approach is the use of relatively complex organic molecules, which is actually analogous to the first approach.…”
Section: Next-generation Rfb Active Chemicalsmentioning
confidence: 99%
“…The next-generation of RFB chemistries are likely to be engineered molecules or complexes, since this approach enables one to shift the SRP to a more desirable potential. One approach that has been utilized to do this is ligand-modified transition metals, which can be dissolved in aqueous 19 or non-aqueous 20 electrolyte solutions. Another promising approach is the use of relatively complex organic molecules, which is actually analogous to the first approach.…”
Section: Next-generation Rfb Active Chemicalsmentioning
confidence: 99%
“…In this work, we seek to substantially decrease both materials and assembly costs by exploring novel membraneless electrolyzer designs. In addition to eliminating the material costs of membranes and associated components, a membraneless electrolyzer can significantly relax design constraints associated with an MEA-based electrolyzer, opening up the possibility for a substantially simplified overall device that is amenable to low-cost, high volume assembly and manufacturing.Membraneless co-laminar flow-cells based on flow-by band electrodes have been demonstrated for fuel cell [20][21][22][23][24] and flow battery [24][25][26][27] applications. These studies revealed the potential for efficient membraneless device operation without significant crossover of species between the anode and cathode, but face significant challenges to scale-up beyond microfluidic applications.…”
mentioning
confidence: 99%
“…Membraneless co-laminar flow-cells based on flow-by band electrodes have been demonstrated for fuel cell [20][21][22][23][24] and flow battery [24][25][26][27] applications. These studies revealed the potential for efficient membraneless device operation without significant crossover of species between the anode and cathode, but face significant challenges to scale-up beyond microfluidic applications.…”
mentioning
confidence: 99%
“…There has been strong evidence that organic compounds can be combined with perovskite oxides via coordination chemistry without altering the crystalline structure. For example, Fe and Co were respectively functionalized with triethanol amine and 1‐[bis(2‐hydroxyethyl)amino]‐2‐propanol in 5M sodium hydroxide solutions .…”
Section: Perovskite Oxide Structurementioning
confidence: 99%